Pendampingan Branding untuk Meningkatkan Citra dan Keberhasilan UMKM Dapur Gemilang Fitriyah - Muhammad Thoriq Ardiazza; Yanda Bara Kusuma (PT. ALHAFI BERKAH INDONESIA, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are crucial in many economies, generating jobs, promoting economic growth, and empowering local communities. Yet, they struggle to stand out amidst tough competition. Thus, establishing a robust brand identity through effective branding is essential. Branding assistance involves professionals aiding MSMEs in understanding their core values, crafting consistent brand messages, and designing fitting marketing strategies to appeal to customers. This support aims to enhance the recognition and competitiveness of Dapur Gemilang Fitriyah MSMEs. The research utilized a qualitative approach with a case study design, gathering primary data through interviews with business owners and relevant parties. Secondary data was also obtained through literature reviews on branding and mentoring for MSMEs. Results showcased the creation of attractive label designs and a company profile website as effective marketing tools for Dapur Gemilang Fitriyah MSMEs. This is expected to elevate the brand's image, product appeal, and expand its market outreach. Through branding assistance, Dapur Gemilang Fitriyah MSMEs can thrive and excel in an increasingly competitive market.